Evaluation of Mutton Quality Characteristics of Dongxiang Tribute Sheep Based on Membership Function and Gas Chromatography and Ion Mobility Spectrometry - Lu, Zengkui; Li, Jianye; Yuan, Chao; Xi, Bin; Yang, Bohui; Meng, Xianyu; Guo, Tingting; Yue, Yaojing; Gao, Yaqin; Liu, Jianbin; Sun, Xiaoping (Frontiers in Nutrition, 2022)
Dongxiang tribute sheep have a history of use in food dishes such as “Dongxiang Handgrip”, which dates back hundreds years and is a favorite halal food in northwestern China. However, little is known about the mutton quality characteristics of Dongxiang tribute sheep. Here, we measured the sensory characteristics, nutritional quality and flavor substances to comprehensively evaluate the mutton quality characteristics of these sheep. The mutton qualities of Dongxiang tribute, Tibetan, Ujumqin and Hu sheep were comprehensively evaluated by membership function. Subsequently, the volatile components in mutton samples from 30 Dongxiang tribute sheep were detected via gas chromatography and ion mobility spectrometry (GC-IMS), and their fingerprints were established. Membership functions were calculated for ten physical and chemical indexes of mutton quality, and the comprehensive membership function values of the four breeds in order of highest to lowest mutton quality were Tibetan sheep (0.76) > Dongxiang tribute sheep (0.49) > Hu sheep (0.46) > Ujumqin sheep (0.33). Thirty volatile compounds were identified via GC-IMS: 7 alcohols, 8 aldehydes, 5 ketones, 2 esters, 2 phenols, 1 ether, 1 furan, 1 acid, 2 hydrocarbons and 1 pyrazine. Ketones, aldehydes and alcohols were the main volatile compounds forming the flavor of Dongxiang tribute sheep mutton. The reliability of the results was validated by PCA (principal component analysis) and similarity analyses. Our results provide reference value for consumers of mutton sheep in China.